The Smurfs in 3D = Şirinler 3D - Gosnell, Raja (Hollywood : Columbia Pictures, 2011)
When the evil wizard Gargamel chases the tiny blue Smurfs out of their village, they tumble from their magical world into New York City.
Region 2.
3-6.
K-3.
Languages : Turkish, English, Hebrew, Hungarian, Slovak, Arabic, Czech, Polish.
Subtitles : Turkish, English, Hebrew, Hungarian, Slovak, Arabic, Czech, Polish.
Keywords: Movie -- animated films; Movie -- Fantasy -- Kids; Smurfs -- Animated movie